2007
DOI: 10.1158/1535-7163.mct-07-0044
|View full text |Cite
|
Sign up to set email alerts
|

O 6-Methylguanine-DNA-methyltransferase promoter demethylation is involved in basic fibroblast growth factor–induced resistance against temozolomide in human melanoma cells

Abstract: Basic fibroblast growth factor (bFGF) is a multifunctional protein and one of the most important growth factors in cutaneous melanoma development and progression. We hypothesized that high bFGF expression might be responsible for chemoresistance in advanced melanoma. M14 human melanoma cells expressing low levels of bFGF were successfully transfected with vectors encoding either the 18 kDa or all isoform proteins of bFGF. M14 cells and bFGF-overexpressing clones had a similar growth rate in vitro. Overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…6,7,9 Temozolomide, a DNA-alkylating agent, inhibits tumor growth by its ability to add methyl groups to the O 6 position of guanines. 3,[12][13][14]40,41 In addition, TMZ induces autophagy. 18 Thus, it has been proposed that the autophagic pathway plays a role in the cytotoxic effects of TMZ.…”
mentioning
confidence: 99%
“…6,7,9 Temozolomide, a DNA-alkylating agent, inhibits tumor growth by its ability to add methyl groups to the O 6 position of guanines. 3,[12][13][14]40,41 In addition, TMZ induces autophagy. 18 Thus, it has been proposed that the autophagic pathway plays a role in the cytotoxic effects of TMZ.…”
mentioning
confidence: 99%
“…9). In addition, growth factor-mediated signaling has been reported to induce resistance in tumor cells (10,11). Other studies have also shown that the transcription factor hypoxia-inducible factor-1α (HIF-1α) and its downstream gene products [e.g., MDR1 and vascular endothelial growth factor (VEGF)] were responsible for drug resistance (12,13) and angiogenesis under hypoxic conditions (14).…”
mentioning
confidence: 99%
“…For comparison of cytotoxicity and establishment of the leader compound the organotin complexes 3 , 4 , 6 , 7 based on 2,6‐di‐ tert ‐butyl‐4‐mercaptophenol were also tested against 8 types of human cancer cell lines. The activity was compared with literature data for cisplatin …”
Section: Resultsmentioning
confidence: 99%